The Effect of Payment Convenience on Online Shopping Addiction Through Marketplace Platform Customer Satisfaction an Intervening Variable in Urban Communities in South Sulawesi - Fani, Rezki; Razak, Darmianti (PT. Maju Malaqbi Makkarana, 2025)
This study aims to examine the effect of ease of payment on online shopping addiction through the intervening variable of marketplace platform customer satisfaction in urban communities in South Sulawesi using the Path Analysis method using SmartPLS 4.0 software. with PLS-SEM Alogarithm and Bootstraping calculations with a sampling method using Nonprobability Sampling Technique of 214 respondents where data was obtained via google form with measurements using a Likert scale. The results of this study indicate that there is no direct effect of payment convenience on online shopping addiction in urban communities in South Sulawesi. Payment convenience affects customer satisfaction. Customer satisfaction affects online shopping addiction in urban communities in South Sulawesi. Payment convenience affects online shopping addiction through customer satisfaction as an intervening variable in urban communities in South Sulawesi